ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP LOAN LOSS PROVISIONS (Studi pada Bank Konvensional yang Terdaftar di Direktori Perbankan Indonesia Periode 2011-2015) - Dewi P, Intan; Indriani, Astiwi (Diponegoro Journal of Management, 2016)
This study aims to examine the effects of  Size, Capital Adequacy Ratio, Loan to Deposit Ratio, Non Performing Loan, and Earning Before Tax and Provision to Loan Loss Provisions on conventional banks listed on Indonesian Banking Directory in 2011-2015. The population is 56 conventional banks in Indonesia.The sampling technique was conducted by using purposive sampling method. The total number of samples in this study is 31 conventional banks. The data was processed using multiple linear regression analysis through classic assumption test before.The results show that NPL and EBTP have positive and significant effect to LLP, while SIZE,   CAR,and   LDR has positive but insignificant effect to LLP. The score of adjusted R Square is 45,3% which means this number could explain the effect  of the variables to LLP.